A manikin study comparing the performance of the GlideScope®, the Airtraq® and the C-MAC® in endotracheal intubation using suction-assisted laryngoscopy airway decontamination techniques in a simulated massive haematemesis scenario by emergency doctors. Issue 5 (September 2021) - Wong, Ching Hin Kevin; Ko, Shing; Wong, Oi Fung; Ma, Hing Man; Lit, Chau Hung Albert; Shih, Yau Ngai
Background: The suction-assisted laryngoscopy and airway decontamination (SALAD) techniques (level 1, SALAD-1 and level 2, SALAD-2) are newly proposed airway management skills to facilitate endotracheal intubation in patients with massive haematemesis. A pilot study using GlideScope ® demonstrated the superior performance of SALAD-1 technique in massive haematemesis simulation. Objectives: To compare the performance of three different video laryngoscopes (the GlideScope ®, the Airtraq ® and the C-MAC ® ) in endotracheal intubation using SALAD techniques by emergency doctors in a manikin simulating massive haematemesis. Methods: Forty-eight emergency doctors were recruited. The participants' performance of endotracheal intubation using the GlideScope ®, the Airtraq ® and the C-MAC ® with the conventional and the two SALAD techniques in a manikin simulating massive haematemesis was evaluated. The time for intubation, number of attempts, rate of failed intubation, amount of aspirated fluid and the subjective ease of different devices and techniques were compared. Results: The C-MAC ® had shorter intubation time compared with GlideScope ® when using conventional (mean intubation time: 28.48 vs 47.00 s, p = 0.018) and SALAD-1 technique (mean intubation time: 29.35 vs 43.25 s, p < 0.039). The intubation time of all three video laryngoscopes was similar in SALAD-2 technique. There was no significant difference in the number of attempts and failed intubation rate among different video laryngoscopes in using different techniques. Intubation with the C-MAC ® resulted in the least mean amount of aspiration in all the conventional (35.63 mL), SALAD-1 (14.06 mL) and SALAD-2 (18.13 mL) techniques. However, the results were not significantly different from the GlideScope ® and the Airtraq ® . The C-MAC ® was rated the most favourable video laryngoscope for the SALAD-1 technique (p < 0.001). There was no significant preference for different video laryngoscopes in using the SALAD-2 technique (p = 0.111). Conclusion: All the video laryngoscopes have similar intubation performance with the SALAD-1 and SALAD-2 techniques. The C-MAC ® performed better than GlideScope ® in terms of intubation time. The C-MAC ® was the most favourable video laryngoscope for the SALAD-1 technique.